Pour l'honneur? Duelling in the army of Napoleon - Bert Gevaert (Bern Open Publishing, 2018)
Duelling and Napoleonic history go together like a horse and carriage. Though strictly forbidden and disliked by Napoleon, duelling was a very frequent phenomenon in the Grande Armée. It is even possible to speak about a 'duellomanie', which caused many (deadly) victims. Nevertheless, for various reasons soldiers crossed blades and duels went according to certain unwritten rules. After an official invitation to go to a certain place at a certain time, a duel, fought with specific weapons, took place under the watchful eye of seconds. Sometimes these duellists wanted to kill their opponent, but in many duels the only intention was to cause a (light) wound. Although duels were honourable and a symbol of masculinity and bravery, they also caused many soldiers to die, not for their country, but in a fight without purpose.